Influence of scaffold composition over in vitro osteogenic differentiation of hBMSCs and in vivo inflammatory response. (May 2014) - Costa-Pinto, Ana R; Vargel, I; Tuzlakoglu, K; Correlo, VM; Sol, PC; Faria, S; Piskin, E; Reis, RL; Neves, Nuno M
To understand the role of chitosan in chitosan-poly(butylene succinate) scaffolds (50% wt), 50%, 25%, and 0% of chitosan were used to produce different scaffolds. These scaffolds were in vitro seeded and cultured with human bone marrow stromal cells in osteogenic conditions, revealing that higher percentage of chitosan showed enhanced cell viability over time, adhesion, proliferation, and osteogenic differentiation. Scaffolds were also implanted in cranial defects and iliac submuscular region in Wistar rats, and the results evidenced that chitosan-containing scaffolds displayed mild inflammatory response and good integration with surrounding tissues, showed by connective tissue colonization and the presence of new blood vessels. Scaffolds without chitosan-evidenced necrotic tissue in scaffolds' interior, proving that chitosan exerts a positive effect over cell behavior and displays a milder host inflammatory response in vivo.